Iridium−Rhodium Nanoparticles for Ammonia Oxidation: Electrochemical and Fuel Cell Studies. Issue 5 (21st February 2017) - Silva, Júlio César M.; Assumpção, Mônica H. M. T.; Hammer, Peter; Neto, Almir O.; Spinacé, Estevam V.; Baranova, Elena A.
Abstract: This study reports the use of carbon‐supported IrRh/C electrocatalysts with different iridium‐to‐rhodium atomic ratios (0 : 100, 50 : 50, 70 : 30, 90 : 10, and 100 : 0) for ammonia electro‐oxidation (AmER) in alkaline media. The materials prepared by using the sodium borohydride method showed a mean diameter of 4.5, 4.8, 4.2, and 4.5 nm for Ir/C, Ir90 Rh10 /C, Ir70 Rh30 /C, and Ir50 Rh50 /C, respectively. According to electrochemical and fuel cell experiments, the Ir50 Rh50 /C catalyst was the most promising towards AmER. This catalyst, which consisted predominantly of the metallic Ir/Rh phases, showed a 500 % higher current density and 55 % higher maximum power than that obtained for Ir/C. After 8 h galvanostatic electrolysis, 93 % of initial ammonia was degraded when using Ir50 Rh50 /C, whereas it was only 70 % with Ir/C. The high activity of the Ir50 Rh50 /C is attributed to a synergic effect of two metals at this iridium‐to‐rhodium ratio, which enhances the kinetics of AmER contributing towards ammonia dehydrogenation at lower potentials. Abstract : Fuel for thought : Carbon‐supported IrRh nanoparticles (IrRh/C) with different iridium‐to‐rhodium atomic ratios (0 : 100, 50 : 50, 70 : 30, 90 : 10, and 100 : 0) are synthesized, and their catalytic activity towards ammonia electro‐oxidation is evaluated. IrRh/C is then further evaluated in a direct ammonia fuel cell.